Interaction with lectins and differential wheat germ agglutinin binding of pyocin 103-sensitive and -resistant Neisseria gonorrhoeae. - Connelly, M C (1981)
Strains of Neisseria gonorrhoeae were treated with pyocin 611 131 (pyocin 103) from Pseudomonas aeruginosa PA103, and isogenic resistant variants were isolated. The interaction of pyocin-sensitive and isogenic pyocin-resistant strains with wheat germ agglutinin (WGA) agglutinated all pyocin-sensitive, but not pyocin-resistant, strains. Binding of WGA to three pyocin-sensitive strains and their isogenic pyocin-resistant variants was examined quantitatively by using fluorescein-conjugated lectin. Pyocin-resistant strains maximally bound one-third to one-eighth the quantity of WGA bound by isogenic-sensitive strains. Linear Scatchard plots revealed homogeneous WGA-binding sites on three pyocin-sensitive and one pyocin-resistant strains. Biphasic Scatchard plots, obtained with two pyocin-resistant strains, show that WGA-binding sites in these strains are heterogeneous. The number of WGA-binding sites for pyocin-sensitive organisms ranged from 8 x 10(5) to 1 x 10(6) sites per coccus and from 1 x 10(5) to 3 x 10(5) sites per coccus for pyocin-resistant strains. The apparent association constant for WGA binding to pyocin-sensitive strains ranged from 3 x 10(6) to 6 x 10(6) liters/mol and from 6 x 10(6) to 1 x 10(7) liters/mol for pyocin-resistant strains. Gonococcal lipopolysaccharide was shown to serve as the pyocin 103 receptor by inhibition of pyocin activity. Lipopolysaccharide from a pyocin 103-resistant strain was not able to inhibit pyocin 103 activity. Pyocin 103 resistance was correlated with a structural alteration involving N-acetylglucosamine residues in gonococcal lipopolysaccharide. Based on interactions with wheat germ, soybean, and ricin lectins, a model of lipopolysaccharide structure in N. gonorrhoeae is presented.